2012
DOI: 10.1038/leu.2012.356
|View full text |Cite
|
Sign up to set email alerts
|

The role of HOX genes in normal hematopoiesis and acute leukemia

Abstract: 20The HOX genes are a highly conserved family of homeodomain-containing 21 transcription factors that specify cell identity in early development and, subsequently,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
261
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(270 citation statements)
references
References 128 publications
6
261
0
1
Order By: Relevance
“…This is fully compatible with the involvement of the HoxA family in stem cell expansion and leukemogenesis. [35][36][37][38] Using RNA interference-based functional screening, Cellot et al 39 identified the H3K4 demethylase JARID1B as a negative regulator of HSC functions among the Jumonji domain-containing family of histone demethylases. The shRNA-mediated knockdown of JARID1B leads to the in vitro expansion of HSCs, which is accompanied by the upregulation of HoxA7, HoxA9, and HoxA10, with preserved long-term reconstitution potential.…”
Section: Discussionmentioning
confidence: 99%
“…This is fully compatible with the involvement of the HoxA family in stem cell expansion and leukemogenesis. [35][36][37][38] Using RNA interference-based functional screening, Cellot et al 39 identified the H3K4 demethylase JARID1B as a negative regulator of HSC functions among the Jumonji domain-containing family of histone demethylases. The shRNA-mediated knockdown of JARID1B leads to the in vitro expansion of HSCs, which is accompanied by the upregulation of HoxA7, HoxA9, and HoxA10, with preserved long-term reconstitution potential.…”
Section: Discussionmentioning
confidence: 99%
“…Hox family regulates genes which control the anterior-posterior body plan and assign tissue fate in human (61). Dysregulation of Hoxa9 has been found in more than 50% of AML patients and highly predicts worse survival (62).…”
Section: Abnormally Spliced (As) Mrnas In Amlmentioning
confidence: 99%
“…[11][12][13][14][15][16] One such approach is to express a HOX protein that confers a benign proliferative advantage to the modified cells over the non-transduced cells in vivo. 15,17,18 HOXB4 was the first HOX family member found to enhance the expansion of human and mouse HSCs by promoting self-renewal divisions without losing stemness. 19,20 Certain fusion proteins of HOXB4 have also been shown to induce expansion of hematopoietic stem cells in vitro.…”
Section: Introductionmentioning
confidence: 99%